Revolutionary copper collection for water remediation through chronoamperometric adsorption with ion-imprinted polymers - Ibrahim, Izwaharyanie; Lim, Hong Ngee; Kamaruzaman, Sazlinda; Pandey, Shyam S. (Elsevier, 2024)
Climate change leads to more frequent and intense extreme weather events like floods and droughts, which can transport copper (Cu) from soils, sediments, and urban areas into water bodies, and raise copper concentrations during dry periods. Both events may cause an increase in Cu contamination risks in water sources. Therefore, it is paramount significance to mitigate the hazards of Cu pollution in water source by developing an effective method for adsorbing Cu(II) from water bodies. Here, we developed an electrochemical adsorption strategy to achieve this goal by Cu(II) ion-imprinted polymer (Cu-IIP) electrode as mediator. Cu-IIP powders were synthesized by blending two naturally occurring biopolymers, cellulose and sodium alginate (SA), with Cu(NO3)2, epichlorohydrin (ECH), and ethylenediaminetetraacetic acid disodium salt dihydrate (EDTA) serving as the source of template ions, cross-linker, and extraction agent, respectively. IIP were then utilized as adsorbents for Cu(II) at a constant cell voltage under electrochemically controlled reduction process. The findings revealed that the IIP/CC exhibits a maximum adsorption capacity of 31.5 mg/g, showcasing efficient electrodeposition of Cu(II) onto the IIP surface at a concentration of 70 mg/L. These indicate that IIP exhibited excellent adsorption capabilities of Cu(II) ions, enabling the effective and efficient enrichment of Cu(II) in water.